2D Accordion‐like MXene Nanosheets as a Sensitive Electrode Material for Baicalin Sensing. Issue 5 (9th February 2021) - Shi, Yan‐Mei; Zhang, Xi; Mei, Lin; Hu, Kai; Chao, Li‐Qin; Li, Xiu‐Min; Miao, Ming‐San
Abstract: Herein, accordion‐like MXene nanosheets was used as electrode sensing material for baicalin determination in traditional Chinese medicine preparation for the first time. The consecutive multilayer nanostructure of MXene observably enhanced the electroactive surface area of electrode and accelerated the electron transfer rate to acquire outstanding electrochemical response to baicalin. The electrode process of baicalin and relative dynamic parameters were investigated using cyclic voltammetry and chronocoulometry. Under optimized conditions, a good linear relationship was achieved between the response current and baicalin levels over the range of 0.08–60 μM with a detection limit of 26 nM (S/N=3). The developed sensor was successfully applied for baicalin monitoring in traditional Chinese medicine preparation and human urine samples. Abstract :